Formation Of National and Citizen Identity During The Period Of Global Changes - Primov Bakhriddin Abdrakhmonovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article emphasizes the fact that the era of global change occurs simultaneously with the age of rapid exchange of information; the destinies of peoples are closely connected with each other. One of the important signs is the increasing status of national and civic identity in the world. We believe that one of our research tasks is to explain, based on our views, the powerful influence of globalization and informatization on this.